Mimari Tasarımda Bina Kabuğu Seçiminin Önemi ve Bina Ekonomisi Üzerindeki Etkisi - BOSTANCIOĞLU, ESRA (My University, 2010)
Choosing the right thickness for insulation on buildings as a preventive measure; should be accentuated in order to prevent pollution and changes in climate; which are among the most important problems of our time, and also to be able to reduce energy consumption to the minimum level possible. The designs made by students should be ensured to identify the building envelope that would provide climatic comfort conditions and would reduce energy consumption as well as life cycle costs. The study aims to identify the changes that can be seen in the initial cost, operational cost and life-cycle costs of buildings by changing the building envelope specifications, which affects not only the initial investment costs but also the operational costs. To this end, the building initial investment, operational and life-cycle costs were identified and assessed by changing the body and insulation materials used in walls, two of the structural components making the building envelope in residential buildings. In addition, the share of insulations and external walls in initial investment costs were compared. The savings in annual fuel costs do not increase at the same rate with the increase in the insulation material thickness.
Keywords: Insulation thickness; life-cycle cost; annual heating cost; initial investment cost; energy saving